Gradual information diffusion across commonly owned firms - Ying, Jie (Journal of Financial Economics, 2024)
This paper studies how common institutional ownership (CIO) affects information diffusion in the stock market. My findings suggest that CIO can exacerbate the slow spread of information across firms. With over 50% of institutional investors holding concentrated stock portfolios, I infer a fundamental connection among firms with CIO. These firms exhibit cross-predictability in monthly stock returns, leading to a CIO-based peer momentum strategy that outperforms Ali and Hirshleifer's (2020) shared-analyst momentum strategy. This anomaly stems primarily from institutional investors with fewer stock holdings, who employ passive asset management characterized by lower portfolio turnover and more delegated investment.